Inside Back Cover: Biotechnology Journal 9/2019. Issue 9 (2nd September 2019) - Hemmerich, Johannes; Tenhaef, Niklas; Steffens, Carmen; Kappelmann, Jannick; Weiske, Marc; Reich, Sebastian J.; Wiechert, Wolfgang; Oldiges, Marco; Noack, Stephan
Abstract : Miniaturization and automation are key technologies to cope with the high number of potentially improved production strains produced by modern genetic engineering tools. In article1800428, Hemmerich et al. present a novel workflow for automated, repeated low‐volume sampling of microtiter plate cultivations. The high degree of parallelization without compromising experimental throughput enables rapid and quantitative phenotyping of larger strain libraries, which is particularly important in the early stages of bioprocess development. The cover image was designed by Verena Resch (http://luminous‐lab.com/ ).